Internet of Things to Explore Moment 2 of “WHO My Five Moments” for Hand Hygiene - Florea, Olga; Gonin, Jeremy; Tissot Dupont, Hervé; Dufour, Jean Charles; Brouqui, Philippe; Boudjema, Sophia (Frontiers in Digital Health, 2021)
Background: Electronic hand hygiene surveillance systems are developing and considered to be more reliable than direct observation for hand hygiene monitoring. However, none have the capability to assess compliance in complex nursing care. Materials and Methods: We combined two different technologies, a hand hygiene monitoring system (radiofrequency identification, RFID) and a nursing care recorder at the bedside, and we merge their data to assess hand hygiene performance during nursing. Nursing tasks were classified as standard task procedures or aseptic task procedures corresponding to moment 2 among the five moments for hand hygiene recommended by the WHO. All statistical analyses were performed using R, version 3.6.2. For mixed models, the package “lme4” was used. Results: From the merged database over the 2-year study period, 30,164 nursing tasks were identified for analysis, 25,633 were classified as standard task procedures, and 4,531 were classified as aseptic task procedures for nursing care. Hand disinfection with an alcohol-based solution was not detected with our system in 42.5% of all the recorded tasks, 37% of all the aseptic task procedures, and 47.1% of all the standard task procedures for nursing (p = 0.0362), indicating that WHO moment 2 was not respected in 37% of mandatory situations. Conclusion: Using a combination of different technologies, we were able to assess hand hygiene performance in the riskiest circumstances.